STUDI MENGENAI PENERAPAN GREEN LOGISTICS DALAM PENANGANAN LIMBAH SISA IKAN DI TPI TUMUMPA - Stephanie Kaligis; Rhainaldy Satikens; Prudensy Opit (Fakultas Teknik Universitas Katolik De La Salle Manado, 2018)
Fish auction (TPI) Tumumpa is a place for dismantling, auctioning and marketing fish under the supervision of Technical Implementation Unit (UPTD). Based on the results of observations and interviews conducted by the authors at TPI location, waste generated by TPI in the form of remnants of fishes is only discarded at the sea by the workers and fishermen. In this research, the authors study about the practice of Green Logistics in PTI Tumumpa and distribute questionnaires to the UPTD. Based on the analysis of the questionnaires, 4 out of 5 staffs of UPTD still puzzle about Green Logistics. Furthermore, the authors find that the place of waste disposal in TPI location is unable to accommodate the waste from TPI. This is happened because the waste is only transported every 6 days. This makes the workers and/or fishermen dispose their waste at the sea.